Le Système immobilier britannique au miroir du système français : la fin d’une exception ? - David Fée (Revue Française de Civilisation Britannique)
The British housing system has undergone major changes since the 1980s that have altered the balance between the three tenures. The political choices made since then have contributed to the dominance of owner-occupation until 2010 before leading to its decline. Social housing has become more diversified and the private rented sector has enjoyed a revival, fuelled by the expansion of buy-to-let programmes. All these changes paradoxically have put an end to a British exception in the housing field and brought France and the UK closer. Meanwhile, the French housing system has adopted certain British specificities, reinforcing their convergence. However, compared to France, the UK retains a number of specific features, including housing finance.